Overview of Nurses' Workload in the Emergency Room (IGD) and Isolation Room During Pandemic Covid-19 Hospital Major General H.A Thalib Full River City - Lianti, Tori; Mawarti, Indah; Nurlinawati, Nurlinawati (Jurnal Keperawatan Universitas Jambi, 2025)
Covid-19 data in Kerinci Regency, Jambi Province In 2021 from January-September positive Covid-19 patients in Kerinci Regency as many a 576 people At Mayjen H.A Thalib General Hospital in 2021 Covid-19 sufferers as many as 170 people with 45 suspected and 11 people died, while in 2021 there was an increase of 481 people wiyh 25 suspected and 85 people dying. This causes an increase in the workload of nurses. This study aims to determine the description of the workload of nurses in the Emergency Room (IGD) and Isolation Room during the Covid-19 pandemic, Mayjen H.A Thalib Hospital, Sungai Penuh City. This study uses a quantitative descriptive design. The stydy was conducted in the Emergency Room (IGD) and Isolation Room of The Mayjen H.A Thalib General Hospital, Sungai Penuh City. With a population of 19 people in the Emergency Room and 21 nurses in the Isolation Room with a sample of 40 nurses. On the physical aspect more than half (65,0%) of the respondents with the physical aspect aevere, on the psychological aspect more than half (75,0%) of respondents with psychologically severe on the aspect of time more than half (60,0%) of respondens with ou who hard working time aspect. Overview of the Workload of Nurses in the Emergency Room and Isolation Room during the Covid-19 Pandemic at the Mayjen H.A Thalib General Hospital in Sungai Penuh City show that more than half (57,5%) of respondents have a heavy workload. It is hoped that this research can be an additional consideration and study of hospital management in implementing good, efficient services in accordance with the workload of nurses at RSU Mayjen H.A Thalib.